Sistem Informasi Penjualan Berbasis Web Dengan Metode Prototype (Studi Kasus : Toko Raya Collection) - Rangga Cahya Gumilang; Indra Cahya Firdaus (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Raya Collection is a micro, small, and medium enterprise (MSME) in the fashion sector that still relies on conventional sales practices, including manual transaction recording and promotion limited to Instagram. These conditions result in low operational efficiency and inadequate delivery of product information to customers. This study aims to design and develop a web-based sales information system to enhance the effectiveness of the business processes. The prototype method was applied to facilitate iterative development and direct evaluation with users throughout the system design stages. The system was developed using PHP as the primary programming language and MySQL as the database management system, supported by tools such as XAMPP, Visual Studio Code, and Visual Paradigm. The evaluation results indicate that the system improves transaction efficiency, expands marketing reach, and provides customers with easier access to product information and online purchasing services. Overall, the proposed system demonstrates greater effectiveness compared to the previous manual sales procedures used by the enterprise.